PENDIDIKAN KARAKTER DALAM KELUARGA (ANALISIS KARAKER TANGGUNG JAWAB) PADA ANAK USIA 6-12 TAHUN DI DESA PULAU KIJANG KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Ora Amputri Silaban; Daeng Ayub Natuna; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine and analyze how high Character Education in the Family (Responsibility Character Analysis) in Children aged 6-12 Years in Desa Pulau Kijang, Kecamatan Kuantan Hilir, Kabupaten Kuantan Singingi and how much is the contribution of Character Education in the Family (Character Analysis of Responsibility). Answer) For children aged 6-12 years in Desa Pulau Kijang, Kecamatan Kuantan Hilir, Kabupaten Kuantan Singingi. This type of research is a descriptive study with a one-variable quantitative approach. The population in this study was 52 parents. Sampling was done using simple random sampling technique, because the sampling of members of the population was done randomly without considering the existing strata in the population. The instrument in this study was a questionnaire or questionnaire containing 49 statements about the character of responsibility which consisted of 5 indicators, including responsibility towards God, oneself, family, society as well as the nation and state. The highest mean value on the indicator of responsibility towards society is 4.30. Based on inferential statistical analysis, the contribution of the responsibility character is classified as moderate with a mean value of 57.66% and the remaining 42.34% is influenced by other indicators besides the indicators in this study.Keywords: Responsibility, Family, Children 6-12 Years